Implementation of Good Corporate Governance Principles in Bank Syariah Indonesia Nganjuk Sub-Branch - Mawadah, Nurmaika Nasyiati; Marsudi, Kenlies Era Rosalina (Institut Agama Islam Negeri Ponorogo, 2023)
Introduction: Insufficient implementation of Good Corporate Governance (GCG) is the cause of financial instability which has an impact on deteriorating bank financial performance and causes failure in GCG implementation. This research aims to find out what factors support and hinder the implementation of GCG in Bank Syariah Indonesia Ahmad Yani Nganjuk Sub-Branch. Research Methods: This research uses qualitative research with a descriptive qualitative approach. The data collection methodology consists of observation, interviews and documentation supported by secondary data sourced from the BSI Syariah website. Result: The results of this research show that the implementation of the five GCG principles can be described as follows: the company is transparent in providing various services, various provisions regarding corporate responsibility have been made and implemented. Fairness indicators have also been given great attention in various aspects. However, in the principles of accountability and professionalism, there are still obstacles, including employees not being punctual and not being disciplined regarding their respective job descriptions. Conclusion: The conclusion of this research is that Bank Syariah Indonesia Nganjuk sub-branch has implemented GCG principles even though there are still several factors that cause some indicators to not be optimal. It is necessary to carry out training, evaluation and work monitoring for employees.